ANALYSIS OF APPROACHES TO THE DEFINITION OF “ADMINISTRATIVE SERVICES” - Kritenko , O.; Brus , T. (Theory and Practice of Public Administration, 2020)
The article deals with the analysis of the normative vision and views of scientists and practitioners on the concept of “administrative services”. Based on such analysis the relationship of administrative services with other types of services, namely: public, state, municipal and social. In the context of the study, the concepts of “administrative services” and “public services” are distinguished. The author’s vision of the concept of “administrative services” is proposed for further study of the system and the process of providing administrative services. Administrative services are interconnected to some extent with public services provided by the state, but semantically the term “public services” comes from a combination of English words “public services”, which can be translated into Ukrainian as “public services”. The concept of “administrative services” and “public services” are distinguished, because we believe that these are not synonymous and not interchangeable concepts because public services are provided in all areas of human-state interaction, in turn, administrative services act as a set of regulations and are provided exclusively at the request of the person. Thus, administrative services are one of the types of public services. Based on the key features of administrative services, taking into account the definition of this definition given by domestic and foreign scholars, we have determined that administrative services are a type of public services provided under the established procedure and in accordance with substantive and procedural requirements. there is an administrative act, the refusal to provide which can be appealed to a higher authority or in court. The normative definition of administrative services is characterized by certain shortcomings, so it needs to be refined in the context of consolidating the term “authority” at the legislative level.